The Effect Of Intellectual, Emotional, And Spiritual Intelligence On The Economic Learning Achievement Of SMA Negeri 1 Soppeng - Satriyani Satriyani; Muh. Yahya; A. Mulyadi Radjab (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2020)
This study aimed to examine the effect of intellectual intelligence on the students’learning achievement, the effect of emotional intelligence on the learning achievement students, the effect of spiritual intelligence on the learning achievement students, and stimulatingly examine the effect of intellectual, emotional, and spiritual intelligence on the economic learning achievement of students in SMA Negeri 1 Soppeng, Soppeng. Afterward, this study included as descriptive quantitative study. Population the study was all students of SMA Negeri 1 Soppeng which is 955 students. For the sample, 90 students were chosenusing simple random sampling technique. Further, data collection techniques used was questionnaire and documentation. Meanwhile, data analysis techniques used was descriptive analysis, analysis test requirements, and data analysis used SPSS 21 program. The result of this study showed that (1) intellectual intelligence variable significantly influenceon the economic learning achievement of students; (2) emotional intelligence variable significantly influencesthe economic learning achievement of students; (3) spiritual intelligence variable significantly effects the economic learning achievement of students; and (4) There was significant variables of intellectual, emotional, and spiritual intelligence on the economic learning achievement. Determination coefficient of X1, X2, and X3 to Y (r2Y.123) was 0,153 which showed that intellectual, emotional, spiritual intelligence factors have contribution to influence the economic learning achievement of students in SMA Negeri 1 Soppeng that was 15,3%, while 84,7% was influenced by another variable that was not analyzed further. DOI: https://dx.doi.org/10.17977/um014v13i12020p050